Analisis Sharia Marketing Mix dalam Upaya Peningkatan Omset Penjualan Toko Dewi Gresik - Intan Dwi Iksanty; Sri Abidah Suryaningsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This reserach aims to analyze the application of Sharia Marketing Mix in efforts to increase sales turnover at Toko Dewi Gresik using the 9P Islamic marketing mix instrument, namely Product, Price, Place, Promotion, People, Process, Physical Evidence, Promise, Patience, as a form of implementing sustainable economic principles. The main focus of this study is to identify and evaluate the Sharia marketing strategies applied by Dewi Store in improving its sales performance. This study uses primary and secondary data sources. Data analysis was conducted using triangulation techniques obtained from interview results to ensure data validity. The results of the study show that the application of the Islamic marketing mix using the 9P indicators in accordance with Islamic business ethics principles has been proven to increase the sales turnover of Toko Dewi Gresik. The Islamic marketing strategy is not only oriented towards achieving economic profits, but also emphasizes aspects of social welfare and prosperity as an effort to realize a sustainable economy.